Democracy derailed in Russia : the failure of open politics - Fish, M. Steven (Michael Steven), 1962- (Cambridge studies in comparative politics., 2005)
Why has democracy failed to take root in Russia? This book shows that Russia's failure to democratize has three causes: too much economic reliance on oil, too little economic liberalization, and too weak a national legislature.